1980
DOI: 10.1152/ajpgi.1980.239.6.g463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serotonin on active electrolyte transport in rabbit ileum, gallbladder, and colon

Abstract: The effect of serotonin on active electrolyte transport was evaluated in vitro in epithelial sheets of rabbit ileum, gallbladder, and colon under short-circuited conditions. Serotonin added to the serosal surface of rabbit ileum caused a dose-dependent short-lived increase in short-circuit current and a more prolonged equal effect on net Na and Cl fluxes. The latter consisted primarily of inhibition of mucosal-to-serosal fluxes of both Na and Cl. In addition serosal serotonin decreased ileal Na influx from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 0 publications
4
34
0
Order By: Relevance
“…Third, tissue damage may have decreased tissue viability and prevented the physiological response to theophylline. However, Shiga toxin caused marked histological damage but the tissue remained responsive to theophylline (Donowitz et al, 1975). The reason for the lack of theophylline response in tissue treated with toxin A is unclear and requires further study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Third, tissue damage may have decreased tissue viability and prevented the physiological response to theophylline. However, Shiga toxin caused marked histological damage but the tissue remained responsive to theophylline (Donowitz et al, 1975). The reason for the lack of theophylline response in tissue treated with toxin A is unclear and requires further study.…”
Section: Discussionmentioning
confidence: 97%
“…Rabbit ileum exposed to Shiga toxin for 5 h in uivo and then mounted in Ussing chambers had decreased transmural PD and tissue resistance and secreted sodium due to an increased s -+ m flux. The change in m + s sodium transport was not significant, even though glucose transport was reduced (Donowitz et al, 1975). C. perfringens enterotoxin also caused secretion of sodium ions in the perfused rat ileum due to an increase in s -+ m flux (McDonel and Asano, 1975); there was no change in the m -+ s flux, even though the toxin had previously been shown to inhibit glucose uptake (McDonel, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that 5-HT stimulated electrogenic Cl Ϫ secretion and inhibited Na ϩ and Cl Ϫ absorption in the rat colon (6), jejunum (7), ileum (8), and guinea pig ileum (9). 5-HT has also been shown to inhibit the NaClabsorptive process in the rabbit ileum and gall bladder (10) but has no effect in rabbit and guinea pig colon (10,11). Moreover, Sundaram et al (12) have demonstrated that 5-HT inhibits Cl Ϫ /HCO 3 Ϫ exchange activity in villus cells and stimulates HCO 3 Ϫ secretion in crypt cells of the rabbit ileum.…”
Section: -Htmentioning
confidence: 99%
“…lumen (Donowitz, Keusch and Binder, 1975;Charney et al, 1976). Injection of the toxin cause haemorrhages in the intestinal mucosa, probably as a result of its cytotoxic activity, and it seems more likely, therefore, that any changes in fluid balance, adenylate cyclase activity and CAMP levels might be a secondary phenomenon (table VI).…”
Section: Figmentioning
confidence: 99%